A companion to Beowulf - Johnston, Ruth A. (Greenwood Press, 2005)
Perhaps the most important work written in Old English, Beowulf grew out of a culture very different from ours, and yet its story of war, violence, and heroism remains relevant to modern readers. Accessible to high school students, general readers, and undergraduates, this companion overviews the poem and its legacy. The initial chapters review the plot of Beowulf, while later chapters discuss its style and language, its cultural and historical contexts, and its afterlife in contemporary popular culture.